Islam and Adat Minangkabau: The Implementation of the Principle Adat Basandi Syarak, Syarak Basandi Kitabullah within the Bundo Kanduang Organization in Minangkabau, 2000–2018 - Butiras Falah; Himayatul Ittihadiyah (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
The Bundo Kanduang Organization represents a prominent women’s institution in Minangkabau society that plays a crucial role in preserving customary law and cultural identity, particularly through the implementation of the philosophical foundation Adat Basandi Syarak, Syarak Basandi Kitabullah. This study aims to examine the historical background of the organization’s establishment and analyze the strategies employed in maintaining and transmitting these values within the community. The research applies Bronislaw Malinowski’s functionalist theory to assess the social functions of the organization. Employing the historical method within a qualitative research framework, the study follows the stages of heuristics, verification, interpretation, and historiography. Data were collected from literature reviews, historical documents, and interviews with traditional leaders and members of Bundo Kanduang. The findings reveal that the Bundo Kanduang Organization functions not only as a custodian of customary law but also as a center of moral and ethical guidance for Minangkabau women and the younger generation. Through its matrilineal kinship system, the organization assumes a strategic role in transmitting Adat Basandi Syarak, Syarak Basandi Kitabullah values via training, cultural education, and community-based programs. These strategies firmly position Bundo Kanduang as a pivotal institution in sustaining the continuity of Minangkabau customary law rooted in this philosophical foundation.